Quang xúc tác phân huỷ MB từ dung dịch nước sử dụng SnO2/BaTiO3 cấu trúc dị thể - Nguyễn Thị Việt Nga; Nguyễn Lê Thanh Hằng; Hồ Thị Thành; Lê Thị Thanh Liễu; NguyễnThị Lan; Phạm Ngọc Thuật; Nguyễn Văn Kim (My University, 2023)
Quang xúc tác phân huỷ MB từ dung dịch nước sử dụng SnO2/BaTiO3 cấu trúc dị thể
Keywords: Quang xúc tác